2013
DOI: 10.1080/0735648x.2013.860046
|View full text |Cite
|
Sign up to set email alerts
|

Support, coercion, and delinquency: testing aspects of an emerging theory

Abstract: This research tests aspects of differential social support and coercion theory of crime as proposed by Colvin, Cullen and Vander Ven (2002). The theory argues social interactions, either coercive or supportive, figure into development of self-control, delinquent behavior, and mental health. Coercive interactions involve force, direct and indirect intimidation and violence that compel compliance out of fear or anxiety. Coercive interactions can be employed consistently or erratically and individuals that are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Each of these 17 questions was coded 1 = yes and 0 = no and summed to produce a summary score for coercion. Although victimization does not tap into the full range of experiencing coercive events, such a conceptualization of coercion has been usefully employed in previous studies of the theory (Baron, , ; Day, Brauer, and Butler, ; Kurtz, Linnemann, and Green, ; Listwan et al., ; Unnever, Colvin, and Cullen, ; Zavala and Kurtz, ). Cronbach's alpha for these items is 0.73, and a principal components analysis revealed a five‐component solution with eigenvalues of 3.31, 1.46, 1.30, 1.12, and 1.06.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these 17 questions was coded 1 = yes and 0 = no and summed to produce a summary score for coercion. Although victimization does not tap into the full range of experiencing coercive events, such a conceptualization of coercion has been usefully employed in previous studies of the theory (Baron, , ; Day, Brauer, and Butler, ; Kurtz, Linnemann, and Green, ; Listwan et al., ; Unnever, Colvin, and Cullen, ; Zavala and Kurtz, ). Cronbach's alpha for these items is 0.73, and a principal components analysis revealed a five‐component solution with eigenvalues of 3.31, 1.46, 1.30, 1.12, and 1.06.…”
Section: Methodsmentioning
confidence: 99%
“…Some may experience coercion for a short period of time, whereas others may experience it for extended periods. The most common form of coercion tested in studies of DCSS is the experience of physical victimization (Baron, , ; Day, Brauer, and Butler, ; Kurtz, Linnemann, and Green, ; Listwan et al., ; Unnever, Colvin, and Cullen, ; Zavala and Kurtz, ). In order to remain consistent with this literature, we will include experiencing victimization as our measure of coercion in this analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some may experience coercion for short periods of time, whereas others may experience it for extended periods. The most common form of coercion tested in studies of DCSS is physical victimization (Baron, 2009a, 2014; Day, Brauer, & Butler, 2015; Kurtz, Linnemann, & Green, 2014; Listwan, Colvin, Hanley, & Flannery, 2010; Unnever, Colvin, & Cullen, 2004; Zavala & Kurtz, 2016). To remain consistent with this literature, we will include physical and emotional victimization as our measures of coercive forces in this analysis.…”
Section: Dcssmentioning
confidence: 99%
“…This study also showed that coercion increases anger, lowered self-control, and serves as a catalyst to seek illegitimate social support. Finally, Kurtz et al (2014) analyzed data from the National Survey of Adolescents and found that interpersonal coercion (physical child maltreatment) predicted delinquency and violent offending, whereas social support reduced the odds of offending.…”
Section: Prior Studiesmentioning
confidence: 99%
“…This study also showed that coercion increases anger, lowered self-control, and serves as a catalyst to seek illegitimate social support. A study by Kurtz, Linnemann, and Green (2014) analyzed data from the National Survey of Adolescents and found that interpersonal coercion (physical child maltreatment) predicted delinquency and violent offending, whereas social support reduced the odds of offending. Finally, Zavala and Kurtz (2016) analyzed data from a sample of police officers and found that coercive forces predicted officer’s perpetration of intimate partner violence.…”
Section: Criticisms and Empirical Testmentioning
confidence: 99%